Implementasi Sistem Informasi Monitoring Kendaraan Dinas Terintegrasi Pada Bank Indonesia Lhokseumawe - Mutasar Mutasar; Novia Hasdyna; Akbar Arafat (Faculty of Computer Science, University of Jember, 2020)
A monitoring system is needed to monitoring vehicle’s daily activities at Bank Indonesia Lhokseumawe. The management of vehicle’s daily activities in the Representative Office of Bank Indonesia Lhokseumawe is still using manual handwritting’s records on some books, which is making it difficult to retrieve the required data quickly and accurately. To assist in carrying out the objection given, the authors designed an integrated information system which capable to monitoring vehicle’s daily activities. The Information system based on web and gps for android.